Implementasi Load Balancing Server Web Berbasis Docker Swarm Berdasarkan Penggunaan Sumber Daya Memory Host - Mohamad Rexa Mei Bella; Mahendra Data; Widhi Yahya (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Virtualization based container is very popular among programming development because this virtualization is lightweight virtualization where Linux kernel allow to share resource between containers so performace container does not interfere with each other. One of the most used virtualization based container is Docker. Docker is open source software which can be change as we wish. Docker container can be used to clustering web server. This method can be used to decrease a single point of failure (SPOF) in web server. However to manage a lot container is complex, but Docker have engine to solve this problem called Docker Swarm. Docker Swarm have internal load balancing but just to manage between container and can't be monitored.So can make resource between host is not unequal distributed. Therefore this research purpose is to distribute web server traffic inside a Docker swarm using loadbalancing based on the resource utilization of the host machine. There are several tests to test the system's functionality and performance in overcoming gaps in failover based time and load balancer based memory. From the test results, we obtained that failover based time and loadbalancer based memory can work in Docker Swarm and can solved the problem about unequal distributed between host.